Pelatihan Platform Canva Untuk Membuat Poster Dan Label Poduk Pada Siswa SMP Muhammadiyah 4 Kertanegara - Adhi Kusuma, Bagus; Rahayu Linda Kusuma; Vita Dwi Utami; Retno Waluyo (PT. Karya Inovatif Nusantara, 2024)
In the modern era like now, there are many activities that use technology, especially in the world of education. Technology is said to be important to apply in the process of teaching and learning activities. Seeing this statement and visiting partners directly, some students are still having problems using technology, especially using the Canva Platform which is often used in the learning process, especially for designing posters and product labels. For this reason, there is a need for training for students to be able to apply technology well. This training was carried out with partners, namely SMP Muhammadiyah 4 Kertanegara, Purbalingga Regency, which was carried out offline. The training participants themselves, namely all grade 8 students, use non-premium Canva so that students do not need to pay to access and search for poster templates and labels to use. The aim of this training is to improve the ability of students at SMP Muhammadiyah 4 Kertanegara to be able to make posters and product labels using the Canva application. The conclusion from this activity is that this activity is useful in introducing the world of graphic design and can improve students' abilities in designing effective and attractive posters and product labels using Canva.